An Age of Risk : Politics and Economy in Early Modern Britain - Nacol, Emily C. (Book collections on Project MUSE., 2016)
In "An Age of Risk", Emily Nacol shows that risk, now treated as a permanent feature of our lives, did not always govern understandings of the future. Focusing on the epistemological, political, and economic writings of Thomas Hobbes, John Locke, David Hume, and Adam Smith, Nacol explains that in seventeenth- and eighteenth-century Britain, political and economic thinkers reimagined the future as a terrain of risk, characterized by probabilistic calculation, prediction, and control. In these early modern sources, Nacol contends, we see three crucial developments in thought on risk and politics. While early modern thinkers differentiated uncertainty about the future from probabilistic calculations of risk, they remained attentive to the ways uncertainty and risk remained in a conceptual tangle, a problem that constrained good decision making. They developed sophisticated theories of trust and credit as crucial background conditions for prudent risk-taking, and offered complex depictions of the relationships and behaviors that would make risk-taking more palatable.